1998
DOI: 10.1086/514944
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicansEndocarditis Associated with a Contaminated Aortic Valve Allograft: Implications for Regulation of Allograft Processing

Abstract: A patient developed Candida albicans endocarditis and fungemia after undergoing aortic valve replacement with an allograft. The allograft had been found during tissue bank processing to be contaminated with C. albicans, but it was culture-negative for C. albicans after routine disinfection with an antifungal-containing antimicrobial solution. Comparison of the preimplantation and postimplantation C. albicans isolates revealed remarkable genetic similarity, but antifungal susceptibility testing showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 10 publications
0
20
0
4
Order By: Relevance
“…Furthermore, DNA fingerprinting with Ca3 fulfills the general requirements set forth in a previous section of this review for effective fingerprinting methods (288). Ca3 and 27A have been used in a number of epidemiological studies of C. albicans and the highly related species C. dubliniensis (see, e.g., references 6,80,137,164,168,192,196,216,218,227,246,265,FIG. 4.…”
Section: Restriction Fragment Length Polymorphisms With Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, DNA fingerprinting with Ca3 fulfills the general requirements set forth in a previous section of this review for effective fingerprinting methods (288). Ca3 and 27A have been used in a number of epidemiological studies of C. albicans and the highly related species C. dubliniensis (see, e.g., references 6,80,137,164,168,192,196,216,218,227,246,265,FIG. 4.…”
Section: Restriction Fragment Length Polymorphisms With Hybridizationmentioning
confidence: 99%
“…Since the banding pattern generated by the C. albicans DNA fingerprinting probe Ca3 (Fig. 6A) has received intense scrutiny using computerassisted systems (137,164,168,192,196,268,329,330,332,336,358), it will be used as a model to describe how complex banding patterns can be analyzed.…”
Section: Analysis Of Complex Banding Patternsmentioning
confidence: 99%
“…13 Apart from bacterial infections, allograft-related virus and fungal infections have also been reported. [14][15][16] The TB infection after allogenic grafts was seen especially after bone and heart valve grafting. 12 Considering the CNS, fatal complications such as prion diseases (Creutzfeldt-Jakob disease) have been reported after allogenic dural grafting 11 but there have been no reports citing allogenic dural graft-related TB in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…While less commonly identified, infections in tissue and eye allografts have also been reported. Tissue transplants associated with transmission of various infections in the US include Candida albicans (Kuehnert et al 1998), Clostridium sordellii (Kainer et al 2004), HCV (Tugwell et al 2005), Epstein-Barr virus (Larsen et al 2007), group A Streptococcus (Lee et al 2007), clostridial endophthalmitis (JAMA 2005), and Chryseobacterium meningosepticum (now Elizabethkingia meningoseptica) (Srinivasan et al, in preparation). In the use of eye tissues, data from 1991 to 2005 showed that primary graft failures (PGFs), endophthalmitis (bacterial and fungal), keratitis, corneal dystrophy/degeneration, and scleral graft rejection were the most common adverse reactions (Hassan et al 2008).…”
Section: Recent Outbreaks Associated With Allograft Transplantationmentioning
confidence: 99%